2023
DOI: 10.1002/psp.2642
|View full text |Cite
|
Sign up to set email alerts
|

Age‐race‐ethnicity segregation in the United States: Where do minority older adults stand?

Abstract: A recent study shows that among the three age groups of youth, adult and older adult, youth‐older adult has the highest age segregation while youth‐adult has the lowest. Similar to many previous age segregation studies, racial‐ethnic differences, an important population axis in segregation studies, were not considered. Prior studies are also limited to using two‐group measures, failing to compare multiple groups together. We explore the complexity in measuring intersectional segregation focusing on the two axe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For Canada, Okraku (2008), introduced gender as well as age and found the existence of distinctive patterns generated by both variables, with higher segregation rates among older women by comparison with the rest of the population. Recently, Wong and Das Gupta (2023) have shown that non-Whites experienced higher age segregation than Whites, while older adults experienced higher racial segregation than the other age groups.…”
Section: Residential Segregation From a Demographic Standpointmentioning
confidence: 99%
“…For Canada, Okraku (2008), introduced gender as well as age and found the existence of distinctive patterns generated by both variables, with higher segregation rates among older women by comparison with the rest of the population. Recently, Wong and Das Gupta (2023) have shown that non-Whites experienced higher age segregation than Whites, while older adults experienced higher racial segregation than the other age groups.…”
Section: Residential Segregation From a Demographic Standpointmentioning
confidence: 99%